Head‐of‐tide bottleneck of particulate material transport from watersheds to estuaries. Issue 24 (23rd December 2015) - Ensign, Scott H.; Noe, Gregory B.; Hupp, Cliff R.; Skalak, Katherine J.
Abstract: We measured rates of sediment, C, N, and P accumulation at four floodplain sites spanning the nontidal through oligohaline Choptank and Pocomoke Rivers, Maryland, USA. Ceramic tiles were used to collect sediment for a year and sediment cores were collected to derive decadal sedimentation rates using 137 Cs. The results showed highest rates of short‐ and long‐term sediment, C, N, and P accumulation occurred in tidal freshwater forests at the head of tide on the Choptank and the oligohaline marsh of the Pocomoke River, and lowest rates occurred in the downstream tidal freshwater forests in both rivers. Presumably, watershed material was mostly trapped at the head of tide, and estuarine material was trapped in oligohaline marshes. This hydrologic transport bottleneck at the head of tide stores most available watershed sediment, C, N, and P creating a sediment shadow in lower tidal freshwater forests potentially limiting their resilience to sea level rise. Key Points: High sediment and elemental deposition occurred in floodplains at head‐of‐tide Low deposition occurred in riverine tidal freshwater forests downstream Tidal flow blocks watershed sediment from reaching tidal wetlands impacted by rising sea level